Monitoring the movements of the building founded on expansive clays - Gorączko, Aleksandra; Gadomska, Maria; Kumor, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the methodology and results of the monitoring of the building, which failed geotechnical reasons. The building is located in Bydgoszcz, and founded into the clays of high expansiveness. Faults in the design of structure and during exploitation led to the activation of the processes of swelling and shrinkage, and consequently the failure state of the structure. After the strengthening of the foundations and repair construction, geotechnical monitoring was conducted, covering, inter alia, systematic measurements of vertical displacements. Monitoring results showed a very slow process of stabilizing movements of the building. This indicates the legitimacy of observation even for several years after the repair of this type of buildings.